Structural and optical properties of copper doped ZnO films derived by sol-gel - Caglar, M.; Yakuphanoğlu, Fahrettin (Elsevier, 2012)
Undoped and copper doped ZnO (ZnO:Cu) films were prepared by sol-gel spin coating technique. The effect of Cu incorporation on the structural, morphological and optical properties of the Zinc oxide ( ZnO) film was investigated. The chemical composition of the Cu doped ZnO films was confirmed by XPS and XRD measurements. The structural disorder was observed in XRD spectra depending on the Cu incorporation and these results were confirmed by the increasing Urbach energy values. The refractive index dispersion was analyzed by single oscillator model developed by Wemple and DiDomenico. The oscillator energy and dispersion energy values for the films were determined. The oscillator energy value E-0 for the ZnO film decreases with Cu incorporation due to increase in the probability of electronic transitions between electronic bands. It is evaluated that the structural and optical properties of ZnO films can be controlled with Cu doping. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: ZnO; Cu doping; Sol-gel; Optical constants; Single oscillator model